Submarine Mass Movements and Their Consequences 2010
DOI: 10.1007/978-90-481-3071-9_40
|View full text |Cite
|
Sign up to set email alerts
|

Southeast Australia: A Cenozoic Continental Margin Dominated by Mass Transport

Abstract: This book, "Submarine Mass Movements and Their Consequences IV", is dedicated to the memory of two colleagues whose wide-ranging field studies did so much to advance our understanding of deep-water sedimentation systems: Drs. Bill Normark and Bruno Savoye. I had the good fortune to count them among my closest professional and personal friends. Both were sea-going scientists par excellence, both were warm and supportive individuals, who always had time for students, and both were modest about their own accompli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…These features are representative of slope failures that occurred in the two dominant slope morphologies present in the study area (see Figure 3) identified by Boyd et al (2010), Clarke et al (2012), and Clarke (2014): a) the relatively steep (3-7°) and canyon-incised slope (Bribie Bowl Slide and Bryon Slide); and b) the relatively gentle slope (1-3°) of the Nerang Plateau (Coolangatta-1, -2 slides and Cudgen Slide). Ten gravity cores from the upper continental slope (<1200 m) were examined in this work (Figure 2), with at least one gravity core recovered from each of the five submarine landslide scars investigated.…”
Section: Study Areamentioning
confidence: 99%
See 4 more Smart Citations
“…These features are representative of slope failures that occurred in the two dominant slope morphologies present in the study area (see Figure 3) identified by Boyd et al (2010), Clarke et al (2012), and Clarke (2014): a) the relatively steep (3-7°) and canyon-incised slope (Bribie Bowl Slide and Bryon Slide); and b) the relatively gentle slope (1-3°) of the Nerang Plateau (Coolangatta-1, -2 slides and Cudgen Slide). Ten gravity cores from the upper continental slope (<1200 m) were examined in this work (Figure 2), with at least one gravity core recovered from each of the five submarine landslide scars investigated.…”
Section: Study Areamentioning
confidence: 99%
“…It extends 1500 km from the Great Barrier Reef to Bass Strait and forms the western continental physiographic boundary of the Tasman Sea. The margin is relatively narrow and typically presents a steep, thinly sedimented upper and middle slope with continental bedrock exposed on its lower slope ( Figure 5) (Boyd et al, 2010;Keene, Baker, Tran & Potter, 2008;Marshall, 1978Marshall, , 1979. The present day morphology of the slope is dominated by erosion and mass wasting (Boyd et al, 2010;Clarke et al, 2012;Glenn et al, 2008;Hubble et al, 2012).…”
Section: Geologic Setting and Margin Structurementioning
confidence: 99%
See 3 more Smart Citations